Technology for Emerging Markets at MSR India - Cutrell, Ed (CSCW 2011: Proceedings of the ACM 2011 conference on Computer supported cooperative work, 2011)
The Technology for Emerging Markets (TEM) group at Microsoft Research India seeks to address the needs and aspirations of people in the world's developing communities. Our research targets people who are just beginning to use computing technologies and services as well as those for whom access to computing still remains largely out of reach. Most of our work falls under the rubric of the relatively young field of Information and Communication Technology for Development (ICTD or ICT4D). Reflecting the interdisciplinary nature of ICTD, TEM is a multidisciplinary group engaged in a range of technical and social-science research. We work in the areas of cultural anthropology, sociology, political science, economics, and psychology, all of which help us understand the social context of technology and how it relates to communities and individual users. We combine this understanding with technical research in hardware and software to devise solutions for underserved communities in rural and urban environments around the world.